MENELUSUR ANOMALI PERTUMBUHAN EKONOMI, INVESTASI, PDRB SEKTOR INDUSTRI DAN UPAH MINIMUM TERHADAP KETIMPANGAN - Andi Lopa Ginting; Andi Faisal Anwar; Jony Puspa Kusuma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Economic growth from year to year continues to move impressively in Makassar City. However, at the same time, economic growth and income distribution have been unbalanced, which has exacerbated the number of economic inequalities that have occurred. The entry of investment, the contribution of the industrial sector and the minimum wage, did not make any significant changes to reduce economic inequality. The purpose of this research is to factually attempt to understand further the effect of investment, economic growth, industrial sector GDP, and minimum wages on the Gini ratio in Makassar City. This study used a kualitative method research model. The novelty of this research is that the search related to economic inequality in Makassar City does not just stop at statistical figures. However, there is also a qualitative in-depth search to understand the real phenomenon of inequality. The results of this study indicate that investment and economic growth as independent variables have a positive effect on the Gini ratio (dependent variable). On the other hand, industrial sector GRDP and minimum wage (independent variable) have no effect on the Gini ratio. Behind the stretch of investment, growth, and the contribution of the industrial sector, these vulnerable poor people get nothing. This growth benefits the middle class more, so that class inequality is increasingly gaping. The loss of income sources in the villages, the low skills and education they have are the main triggers for the low level of income they have. Suggestions and implications of this research are that the Makassar City government should re-design a more inclusive economic growth.